2015
DOI: 10.1186/s40360-015-0017-x
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics and pharmacodynamics of danirixin (GSK1325756) − a selective CXCR2 antagonist − in healthy adult subjects

Abstract: BackgroundExcessive neutrophil presence and activation is important in a number of acute and chronic inflammatory diseases. The CXCR2 chemokine receptor is important in controlling the extravasation and activation of neutrophils. Selective antagonism of the CXCR2 receptor is a potential approach to reducing neutrophil migration and activation. Danirixin, is a small molecule, CXCR2 antagonist being evaluated as a potential anti-inflammatory medicine.Methods(1) First time in human (FTIH) double-blind, placebo-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 14 publications
3
36
0
1
Order By: Relevance
“…In human blood, the pIC 50 of 6.4 in the CD11b assay compared with the more potent values seen in binding or functional assays in purified systems is consistent with the moderately high protein binding observed with danirixin (98% in human plasma). This value is also consistent with the pIC 50 of 6.8 (69 ng/ml) determined by pharmacokinetic/pharmacodynamic modeling in phase 1 (Miller et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In human blood, the pIC 50 of 6.4 in the CD11b assay compared with the more potent values seen in binding or functional assays in purified systems is consistent with the moderately high protein binding observed with danirixin (98% in human plasma). This value is also consistent with the pIC 50 of 6.8 (69 ng/ml) determined by pharmacokinetic/pharmacodynamic modeling in phase 1 (Miller et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…The role of CXCR2 antagonists in altering blood neutrophil levels has been investigated since the first reports of neutropenia in human subjects treated with navirixin (Rennard et al, 2015) or AZD5069 (Kirsten et al, 2015). Neutropenia was not observed either preclinically as described here for danirixin or clinically with either danirixin (Miller et al, 2015) or the related compound elubrixin (Lazaar et al, 2011). The differences in the behavior of these compounds at the CXCR2 receptor, as well as selectivity with respect to CXCR1, may explain the distinct clinical observations.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The dose proportionality following the single oral and intravenous administration of the free base of danirixin has been established in previous studies. 7,10 This study also demonstrated the dose proportionality of danirixin HBr in line with the previous studies. In 1 earlier study, compared to danirixin free base, the HBr salt form of danirixin showed less variability in the PK in spite of higher exposures (92% increase in AUC 0-t and 76% increase in C max ).…”
Section: Discussionsupporting
confidence: 89%
“…The most developed ones, AZD5069 (AstraZeneca), navirixin (Merck Sharpe & Dohme), danixirin (Glaxo-SmithKline), and the combined CXCR1/ 2 inhibitor reparixin (Dompé Farmaceutici S.p.A.) have completed phase I and II studies. Importantly, they displayed beneficial safety profiles without increasing risk of infection (Roberts et al, 2019;Lazaar et al, 2011;Hastrup et al, 2015;Miller et al, 2015). Studies with ozone-or LPS-induced airway inflammation in human volunteers showed that treatment with CXCR2 antagonists reduced neutrophil counts in the lungs by 50-80% (Lazaar et al, 2011;Leaker et al, 2013).…”
Section: Targeting Pro-inflammatory Cytokinesmentioning
confidence: 99%